The Swiss Pavilion - Zumthor, Peter (2000)
Pabellón de Suiza, en la expo Hannover 2000, utilizando madera de pino y alerce
Keywords: ALEMANIA; HANNOVER; EXPOSICIONES INTERNACIONALES; PABELLONES; MADERA; MATERIALES DE CONSTRUCCION; SUIZA